High Variability in Cellular Proliferation, Gene Expression, and Cytokine Production in the Nonneoplastic Colonic Epithelium of Young Apc+/Min-FCCC Mice - Leystra, Alyssa A.; Harvey, Kristen N.; Kaunga, Esther; Hensley, Harvey; Vanderveer, Lisa A.; Devarajan, Karthik; Clapper, Margie L. (Frontiers in Oncology, 2021)
An urgent need exists to identify efficacious therapeutic preventive interventions for individuals who are at high risk of developing colorectal cancer. To maximize the benefits of preventive intervention, it is vital to identify the time interval during which the initiation of a preventive intervention will lead to an optimal outcome. The goal of the present study was to determine if oncogenic events can be detected in the nonneoplastic colonic mucosa of Apc+/Min-FCCC mice prior to formation of the first adenoma, thus defining an earlier point of intervention along the cancer continuum. Tissues taken at three potential points of intervention were characterized: prior to Apc mutation (wild type Apc+/+-FCCC mice); after initiation but prior to colon adenoma formation (tumor-free Apc+/Min-FCCC mice); and after formation of the first colon adenoma (tumor-bearing Apc+/Min-FCCC mice). Experimentation focused on molecular processes that are dysregulated in early colon lesions: 1) cellular proliferation (proliferative index and size of the proliferative zone); 2) cellular stemness (expression of Ascl2, Grem1, Lgr5 and Muc2); 3) EGFR signaling (expression of Ereg); and 4) inflammation (expression of Mmp9, Ptsg2, and Reg4, as well as secretion of 18 cytokines involved in immune activation and response). Interestingly, the nonneoplastic colonic mucosa of wild type, tumor-free Apc+/Min-FCCC, and tumor-bearing Apc+/Min-FCCC mice did not display significant differences in average epithelial cell proliferation (fold change 0.8–1.3, p≥0.11), mucosal gene expression (fold change 0.8–1.4, p≥0.22), or secretion of specific cytokines from colonic mucosa (fold change 0.2–1.5, p≥0.06). However, the level of cytokine secretion was highly variable, with many (22% of wild type, 31% of tumor-free Apc+/Min-FCCC, and 31% of tumor-bearing Apc+/Min-FCCC) mice categorized as outliers (> 1.5 x interquartile ranges below the first quartile or above the third quartile) due to elevated expression of at least one cytokine. In summary, no differences were observed in proliferation, stemness, and EGFR signaling in the colonic mucosa of wild type vs Apc+/Min-FCCC mice, with low baseline cytokine expression, prior to the formation of the first colon adenoma. The results of this study provide valuable baseline data to inform the design of future cancer prevention studies.